The Potential Application of Mung Bean (Vigna radiata L.) Protein in Plant‐Based Food Analogs: A Review - Mohammad Tarahi (Legume Science)
ABSTRACT The increasing demand for plant‐based food products by consumers along with the growing global population requires the discovery of novel and sustainable protein sources to address environmental challenges and meet nutritional requirements. Among various plant proteins, mung bean protein (MBP) exhibits several unique characteristics that make it a valuable ingredient in the field of plant‐based food analogs. This literature review aims to express the unique structure and composition of MBP, in addition to its physicochemical, functional, and nutritional properties. Furthermore, its potential applications in novel meat, dairy, and egg analogs are highlighted to meet the growing demand for sustainable, nutritious, and delicious plant‐based food alternatives. Structurally, MBP consists of a complex arrangement of amino acids, forming a globular protein with distinct functional properties. Its composition is also rich in essential amino acids, particularly leucine and lysine, making it a promising protein source for plant‐based diets. From a techno‐functional perspective, MBP exhibits remarkable gelling, emulsifying, foaming, and binding properties, which are necessary for the development of stable emulsions, airy foams, firm gels, and cohesive textures in various plant‐based food formulations. Moreover, MBP and its derivatives can possess notable bio‐functional properties, including antioxidant activity and anti‐inflammatory benefits, as well as cholesterol‐lowering, anti‐obesity, antidiabetic, antihypertensive, and anticancer effects. Consequently, the production of food analogs based on MBP not only improves the techno‐functional attributes of the final products but also can promote consumer health and well‐being.